2016
DOI: 10.7202/1037660ar
|View full text |Cite
|
Sign up to set email alerts
|

Pratiques de conciliation travail-famille et détresse psychologique des salariés québécois : une comparaison selon le genre

Abstract: Dans le contexte où les couples à deux carrières constituent maintenant la norme, l'enjeu de la conciliation travail-famille devient incontournable. Cette nouvelle réalité souligne la nécessité d'examiner les effets des pratiques de conciliation travail-famille mises en place dans les organisations québécoises sur le bien-être des travailleurs. Une comparaison selon le genre s'avère également pertinente, vu la persistance des rapports sociaux de sexe et de la division sexuell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…These models have been tested in various societal contexts and, even if there is no consensus, many have corroborated that the response to these stressors differs between women and men. For instance, while studies have shown that high psychological demands are related to psychological distress only for men or for women (Michélsen & Bildt, ; Mori, Nakashima, Yamazaki, & Kurita, ; Vézina, Bourbonnais, Marchand, & Arcand, ) others have shown such relationship for women and for men (Boulet & Le Bourdais, ; Bültmann, Kant, Schröer, & Kasl, ; Bültmann, Kant, Van Den Brandt, & Kasl, ; Cohidon, Rabet, Murcia, Khireddine‐Medouni, & Imbernon, ; Stansfeld, Fuhrer, Shipley, & Marmot, ). Some other studies have shown no significant relationship for both women and men (Bildt & Michélsen, ; Choi et al, ; Einarsen & Nielsen, ; Niedhammer, Chastang, David, Barouhiel, & Barrandon, ; Roxburgh, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These models have been tested in various societal contexts and, even if there is no consensus, many have corroborated that the response to these stressors differs between women and men. For instance, while studies have shown that high psychological demands are related to psychological distress only for men or for women (Michélsen & Bildt, ; Mori, Nakashima, Yamazaki, & Kurita, ; Vézina, Bourbonnais, Marchand, & Arcand, ) others have shown such relationship for women and for men (Boulet & Le Bourdais, ; Bültmann, Kant, Schröer, & Kasl, ; Bültmann, Kant, Van Den Brandt, & Kasl, ; Cohidon, Rabet, Murcia, Khireddine‐Medouni, & Imbernon, ; Stansfeld, Fuhrer, Shipley, & Marmot, ). Some other studies have shown no significant relationship for both women and men (Bildt & Michélsen, ; Choi et al, ; Einarsen & Nielsen, ; Niedhammer, Chastang, David, Barouhiel, & Barrandon, ; Roxburgh, ).…”
Section: Introductionmentioning
confidence: 99%
“…As regards the family, most studies on psychological distress among working populations extensively addressed work stressors but either overlooked family stressors or focused on objective aspects such as family status, number of children or number of hours devoted to domestic tasks (Beauregard et al, ; Evans et al, ). For example, Väänänen et al () showed that domestic tasks are linked to the psychological distress among working women only, whereas Boulet and Le Bourdais () found a significant association only among working men. Many studies gave evidence that mothers' distress exceeds that of childless women and that lone‐parent women were more affected than married women or lone‐parent men (Umberson, Pudrovska, & Reczek, ; Umberson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Leurs analyses auprès de 933 parents ont montré que les femmes et les familles des classes moyennes et supérieures estiment plus important d'aménager du temps de qualité avec les enfants dans l'horaire familial. Au Québec, les données récentes démontrent qu'une ambivalence entre les sphères professionnelle et familiale engendre certaines tensions, particulièrement pour les jeunes mères de famille (Boulet et Le Bourdais, 2016;Fortier et Deschenaux, 2016;Moreau, Tahon et Daigle, 2010;Seery, 2014;Tremblay, 2012). Tremblay, Najem et Paquet (2006) ont observé dans l'Enquête sur les milieux de travail et les employés une hausse des heures de travail à la maison entre 1999 et 2002 autant pour les hommes que pour les femmes, les deux groupes accomplissant respectivement, en moyenne, 6,14 et 6,13 heures de travail à la maison.…”
Section: Article Abstractunclassified
“…est particulièrement important. Source de stress et ce, encore plus pour les femmes(Boulet et Le Bourdais, 2016;Kempeneers et al, 2015 ; Van Pevenage, 2010) qui assument davantage les tâches domestiques (Lacroix etBoulet, 2013), la difficile conciliation du travail et de la famille constitue l'une des préoccupations majeures pour les travailleurs, toutes générations confondues…”
unclassified